Perancangan Buku Ilustrasi “Nyanyian Anak Balam Rabab Pasisia“ - Adha Zuhkri Arafad; Budiwirman Budiwirman (Student Research Journal, 2023)
The Balam Rabab Pasisia Children's Song is a folk tale from the Minangkabau people, West Sumatra, South Coast. It is said that the children's singing of Balam is a traditional healing process. In the past, someone from the family who was sick would be taken to a shaman (smart person) to carry out a healing ritual. In line with the development of the Balam Children's Song era, it has now entered the Pesisian rabab performing arts. Besides that, rabab is a performing art that tells stories about kaba from other folk tales. This is what prompted the designer to design the illustrated book ''Nyaniyan Anak Balam Rabab Pasisia''. There are still many among the younger generation who do not know the culture, traditions and folklore because there is a lack of information and dissemination is still not effective. The aim of designing the illustration book "Song of Children's Balam Rabab Pasisia" is to provide information to the Minangkabau community about the story of the Song of Children's Balam Rabab Pasisia, as well as a medium for preserving folklore in Minangkabau society. The design of the illustration "Balam Rabab Pasisia Children's Song" uses the glass box design method with the 5W1H analysis technique. The type of illustration used is a 2D semi-realist cartoon. The output of this design is a book measuring 18 cm x 18 cm which contains narrative and related illustrations to clarify the narrative and also add to the aesthetic value of the book. After carrying out a feasibility test, the results showed that the design was good starting from the colors, illustrations, fonts and layout. And it can be concluded that the Illustrated Book "Children's Songs of Balam Rabab Pasisia" was well received by respondents. In this design there is also supporting media which includes: posters, banners, bookmarks, e-books, t-shirts, tote bags, key chains, tumblers and stickers.